Incidence of preleukemic fusion genes in healthy subjects - Kosik, P; Skorvaga, M; Belyaev, I (Neoplasma, 2016)
The diagnostics of leukemia relies upon multi-parametric approach involving a number of different pathology disciplines such as flow cytometry, histopathology, cytogenetics and molecular genetics [fluorescent in situ hybridization (FISH) and polymerase chain reaction (PCR)]. Childhood leukemia is often determined by the presence of specific chromosomal translocation that entails the generation of preleukemic fusion genes (PFG). In the last two decades, several studies have reported observations that PFG are present in healthy population and not necessarily result in leukemia. The first such study by Limpens and colleagues on t(14/18)/ BCL2-JH [1] and next in line [2, 3] led to many questions regarding the significance of these chromosomal translocations in leukemogenesis. However, the data on the incidence of PFG are contradictive. This review aims to highlight the molecular genetic approaches used by various studies with regard to differences in diagnostics and incidence of PFG in healthy subjects. The focus is on the incidence and prevalence of the most common PFG such as TEL-AML1, MLL-AF4, BCR-ABL (p190), AML1-ETO, PML-RARA, and CBFB-MYH11 detected in umbilical cord blood, in neonatal blood spots (Guthrie cards (GC)), bone marrow, peripheral blood and tissues of amortized fetuses. We conclude that the incidence of PFG is significantly higher than incidence of leukemia and more sophisticated analysis of PFG in leukemogenic cell populations is warranted to relate the occurrence of PFG with leukemia. The emerging notion is that only those PFG may contribute to development of leukemia which arise in stem cells at specific time windows during development. Thus, screening of PFG in subpopulations of stem cells may be a challenge for assessment of predisposition to leukemia and for validation of cell transplant to minimize donor cell-derived leukemia.